Pengaruh Pelapisan Kitosan dan Suhu Penyimpanan terhadap Karakter Fisik Buah Sawo (Manilkara achras (Mill.) Fosberg) Selama Pematangan - Widya Mudyantini; Santosa Santosa; Kumala Dewi; Nursigit Bintoro (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2017)
Sapodilla (Manilkara achras (Mill.) Fosberg) is a climacteric and highly perishable fruit with thin peel. The objectives of this study were: (1) to examine the effect of chitosan coating concentrations and storage temperature on the physical and chemical characteristics of sapodilla and (2) to determine the chitosan coating concentrations and the optimum storage temperature for the storage of sapodilla. Factorial Split-Plot Design was used in this experiment: three levels of storage temperature as the main factors (5 °C, 15 °C, 25 °C) and four levels of chitosan concentrations (0%, 2%, 3%, 4%) as the sub-factors. Each treatment was made in five replicates. Collected data were analyzed using analysis of variance (ANOVA) followed by the Duncan’s Multiple Test (DMRT) at the test level of 5%. Sapodillas used in this study had the same age in the weight of 100-120 grams and were harvested from the same tree. They were observed until rotten. The parameters observed were the concentrations of chitosan coating thickness on sapodillas’peel, the permeability of chitosan membrane to the air water vapour and oxygen, shelf life, hardness, content of chlorophyll and carotenoid, and respiration of the fruit. Observed data showed that the higher chitosan concentrations was used, the higher capability of the sapodilla’s peel to hampered water vapour and oxygen’s to peddix the peel. However, the chitosan coating concentration of 4% and the storage temperature of 5 °C temperature made the chitosan layer flaked. The treated concentrations of chitosan coating (0%, 2%, 3%, 4%) at certain storage temperature variations (5 °C, 15 °C, 25 °C) and their interactions had an effect on the physical characters of sapodilla in all parameters. The higher coated chitosan concentration applied, the hardness of sapodilla increased. The chlorophyll contents of sapodilla peel were increasing along with the hampering of the ripening. When the sapodillas were ripe, the carotenoid contents increated. The oxygen contents were decreasing along with the ripening of the sapodillas. The CO2 contents were increasing along with the ripening process of the sapodillas. The optimum treatment to keep sapodillas’ shelf life was the chitosan coating of 3% and the the storage temperature of 5 °C. ABTSRAKBuah sawo (Manilkara achras (Mill.) Fosberg) merupakan buah klimaterik yang mempunyai kulit tipis dan cepat matang. Tujuan penelitian ini adalah mengkaji pengaruh konsentrasi pelapisan kitosan dan suhu simpan terhadap sifat fisik dan kimiawi buah sawo serta menentukan konsentrasi pelapisan kitosan dan suhu simpan yang paling optimum untuk memperpanjang masa simpan buah sawo. Rancangan penelitian yang digunakan adalah Split Plot Design pola faktorial dengan dua faktor, yaitu suhu penyimpanan terdiri dari tiga taraf (5 °C, 15°C, 25 °C) sebagai faktor utama dan konsentrasi kitosan yang terdiri dari empat taraf (0%, 2%, 3%, 4%) sebagai sub faktor. Setiap kombinasi dengan lima ulangan. Data dianalisis menggunakan Analisis Varian (ANAVA) kemudian dilanjutkan dengan uji Duncan’s Multiple Range Test (DMRT) pada taraf uji 5%. Buah dengan umur fisiologis sama, berat 100 – 120 g dipanen dari satu pohon. Buah diberi perlakuan pelapisan kitosan dan disimpan pada temperatur yang berbeda, selanjutnya diamati sampai buah tidak layak dikonsumsi. Parameter yang diamati adalah tebal lapisan kitosan berbagai konsentrasi pada kulit buah, permeabilitas membran kitosan terhadap uap air dan O2, masa simpan, kekerasan buah, kandungan klorofil dan karotenoid serta laju respirasi. Hasil yang diperoleh menunjukkan semakin tinggi konsentrasi kitosan, semakin terhambat masuknya uap air dan oksigen ke dalam kulit buah, tetapi konsentrasi kitosan 4% dan suhu 5 °C menyebabkan lapisan kitosan mengelupas. Perlakuan konsentrasi pelapisan kitosan (0%, 2%, 3%, 4%) dan suhu simpan (5 °C, 15 °C, 25 °C) serta interaksinya mengakibatkan semakin tinggi konsentrasi kitosan, kekerasan buah sawo semakin meningkat, juga kadar klorofil kulit buah. Semakin buah matang kadar karotenoid semakin meningkat, demikian juga kadar CO2. Kadar oksigen semakin menurun seiring dengan pemasakan buah. Perlakuan optimum untuk mempertahankan masa simpan buah sawo adalah perlakuan pelapisan kitosan 3% dan suhu simpan 5 °C.Kata kunci: Kitosan; karakter fisik; sawo (Manilkara achras (Mill.) Fosberg); suhu